Wang Wei: A Buddhist Poet - Qiu, Sulun (Journal of Sinology (วารสารจีนวิทยา), 2007)
Born in a devout Buddhist family, Wang Wei (A.D.701-761), a famous poet of the Tang Dynasty, gained a good understanding of the Buddhist doctrine at a very young age, prompting him to become a Buddhist poet years later. Although in his early age Wang Wei wrote many works expressing his deep concerns for social life, after suffering from several setbacks in his official career, he turned to the spiritual world and the world of nature and worte more poems describing nature and inserting Buddhist dhamma in his work. This article makes particular appreciative comments on Wang’s poetry, which is infused with dhamma and the idea of nothingness, citing some representative verses which she translate into Thai, for example, "Lu Zhai" or "Deer-Park Hermitage".